Vol. 769 : High Technology: Research and Applications (HTRA 2017): The VI International Science and Engineering Conference, November 27-29, 2017, Tomsk, Russia; [proceedings]; Key Engineering Materials - Osokin G. E. Georgy Evgenievich; Kulinich E. A. Ekaterina Aleksandrovna (2018, 2018)
Title screen